Comparison and Development Trends of Energy Efficiency Characterization Methods for Room Air Conditioners in China and ASEAN Countries - Yang Jie; Chen Yanru; Cheng Jianhong; He Yuan; Li Pengcheng; Xia Yujuan (Zhileng xuebao)
This article introduces the current status of energy efficiency standards and labeling for room air conditioners in China and ASEAN countries. It compares the energy efficiency of room air conditioners in China and ASEAN countries from the aspects of applicable products, testing methods, energy efficiency characterization indicators, and energy efficiency labeling, and analyzes the development trend of energy efficiency standards for room air conditioners. The research results indicate that the energy efficiency standards of Chinese air conditioners are highly consistent with those of most ASEAN countries in terms of energy efficiency evaluation system, testing points, and testing conditions. The main difference is that ASEAN countries only assess refrigeration energy efficiency and refrigeration season. The differences in outdoor temperature time curves are reasonable, but they result in incomparable energy efficiency values. The energy efficiency labels of various countries are based on energy efficiency standards, although the forms are different, there is no substantial difference. The development of energy efficiency standards includes various aspects such as improvement of energy efficiency evaluation system, enhancement of energy efficiency indicators, improvement of testing methods, expansion of product coverage, adaptability of product functions and technological upgrades, etc. Among them, dynamic testing is an important development direction, but the technical difficulty is high and there is a certain degree of uncertainty. The research results can provide reference for further improving the energy efficiency standards of room air conditioners in China and ASEAN countries, and promoting regional coordination.